2004
DOI: 10.1111/j.1365-2893.2004.00509.x
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphism of the MxA gene promoter influences the response to interferon monotherapy in patients with hepatitis C viral infection

Abstract: The biological activity of interferon (IFN) is mediated by the induction of intracellular antiviral proteins, such as 2'-5' oligoadenylate synthetase, dsRNA-activated protein kinase and MxA protein. Among these, MxA protein is assumed to be the most specific surrogate parameter for IFN action. This study was performed to elucidate whether a single nucleotide polymorphism (SNP) (G/T at nt-88) in the promoter region of the MxA gene influences the response to IFN therapy in patients with chronic hepatitis C virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 34 publications
4
57
0
Order By: Relevance
“…Furthermore, association studies have suggested that polymorphisms in these genes may play a role in differential drug response [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, association studies have suggested that polymorphisms in these genes may play a role in differential drug response [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The -88T SNP in the MxA gene was found to be associated with lower MxA activity. In patients with low viral load, sustained viral response (SVR) was significantly higher (62%) in -88T patients than in patients bearing the -88A allele (32%) (11). The 5`2` OAS plays a major role in the clearance of the virus.…”
Section: Host Genetic Factorsmentioning
confidence: 99%
“…Three SNPs in the IFN induced 2'-5' oligoadenylated synthetase -like gene (OASL) (rs3213545 T , rs1169279 A and rs2859398 C alleles) were found to be associated with SVR (Su, Yee et al 2008). The T allele in the promoter (-88) of MxA was also associated with SVR (Suzuki, Arase et al 2004). Although these association studies highlight the relevance of IFN and ISG variants in HCV treatment, additional gene expression studies have been carried out to directly correlated expression levels with treatment outcome.…”
Section: Host and Viral Factors Influencing Treatment Responsementioning
confidence: 99%
“…Underlined HLA alleles appear in more than one study. References: (Thio, Gao et al 2002;McKiernan, Hagan et al 2004;Wang, Zheng et al 2009), (Thio, Thomas et al 2001;Yee 2004;Yoon, Han et al 2005;Ksiaa, Ayed-Jendoubi et al 2007;Harris, Sugimoto et al 2008), (Ishida, Ikebuchi et al 2011), (Falleti, Fabris et al 2010), (Haas, Weiß et al 2009), (Mueller, Mas-Marques et al 2004), (Yee, Tang et al 2001) (Morgan, Lambrecht et al 2008), (Thio, Goedert et al 2004;Paladino, Fainboim et al 2006), (Knapp, Hennig et al 2003;Lio, Caruso et al 2003;Kimura, Saito et al 2006;An, Thio et al 2008), (Schott, Witt et al 2008), (Huang, Yang et al 2007), (Ge, Fellay et al 2009;Mangia, Thompson et al 2010), (Tanaka, Nishida et al 2009;Rauch, Kutalik et al 2010), (Vejbaesya, Nonnoi et al 2011), (Khakoo, Thio et al 2004;Montes-Cano, Caro-Oleas et al 2005), (Persico, Capasso et al 2008), (Su, Yee et al 2008), (Suzuki, Arase et al 2004), (Knapp, Yee et al 2003), (Dai, Chuang et al 2010). The innate immune system has a critical role in detecting pathogens and triggering the immune response.…”
Section: Host Genetic Diversity and Natural History Of Hcv Infectionmentioning
confidence: 99%